The geography of transaction linkages in twelve European case study regions - Patrick Commins; Andrew Copus; Timo Lakso; Marsaili MacLeod; Dimitris Skuras (European Regional Science Association (ERSA), 2003)
Small and medium sized enterprises operate within a complex web of links of various kinds. These may be distinguished in terms of their content (transactional, advisory, regulatory, social), "object" (other SMEs, third sector organisations, business services, local and national government), geography (local,regional, global), and durability (transient, permanent, frequent, irregular). A simpler categorisation might be between "hard" linkages involving a recorded transaction of some kind, and "soft" informal interation involving only information. Several schools of thought on local economic development emphasise either or both these types of interaction as important factors in local development dynamics. This is a particularily important group of concepts in relation to peripheral regions, where local opportunities for interaction are constrained, and longer distance relationships are more difficult and expensive. This paper begins with a review of recent research relating to business networks,focusing as far as possible on work relating to rural and peripheral areas, and including relevant aspects of the concepts of social capital, governance and "institutional thickness". This will be drawn together in the form of a number of hypotheses regarding the role of different forms of interaction in determining the degree of economic vitality in peripheral regions. The validity of these hypotheses will then be examined in the light of case-study data relating to twelve regions (six peripheral, six more accessible) in Scotland, Finland, Germany, Spain and Greece. Drawing predominantly on a survey of 600 SMEs, the discussion is structured into the following four themes: The geography of transactional linkages Other aspects of transactional linkages Links with third sector organisactions Links with local, regional and national government agencies. The paper will conclude with a review of the hypotheses and an integrated assessment of the impact of all kinds of networks on regional economic performance. The information presented in this paper has been derived from research funded by the EU Fifth Framework, as part of project QLK5-2000-00783 - Aspatial Peripherality, Innovation and the Rural Economy (AsPIRE).
Keywords: 330